Compensation and Work Discipline's Effects on Employee Achievement at Perumda Pasar Juara - I Nyoman Tri Sutaguna; Ferdinandus Sampe; Adrian Febriana Dima; Daniel Lallo Pakiding; Muhammad Yusuf (Pascasarjana STIE Amkop Makassar, 2022)
AbstrakPerumda Pasar Juara is a company that offers traditional market services. According to survey, there are several problem phenomena that occur in the company where employees are currently considered not to be able to perform well at work so that they cannot complete all of the tasks assigned to them. This is due to poor employee discipline, which precludes employees from executing multiple tasks assigned to them on time. Moreover, compensation is thought to influence employee performance so when pay is calculated to be standard, making employees lazy to work and eager to find jobs with higher pay. As a research collect data. A Likert scale is employed in the data collection technique. Kata kunci: Work Discipline, Compensation, Work Performance